Reversible Carrier Modulation in InP Nanolasers by Ionic Liquid Gating with Low Energy Consumption - Chia‐Hung Wu; Chi‐Wen Chen; Hung‐Jung Shen; Hsiang‐Yu Chuang; Hark Hoe Tan; Chennupati Jagadish; Tien‐Chang Lu; Satoshi Ishii; Kuo‐Ping Chen (Advanced Science)
Abstract Nanoscale light sources are demanded vigorously due to rapid development in photonic integrated circuits (PICs). III‐V semiconductor nanowire (NW) lasers have manifested themselves as indispensable components in this field, associated with their extremely compact footprint and ultra‐high optical gain within the 1D cavity. In this study, the carrier concentrations of indium phosphide (InP) NWs are actively controlled to modify their emissive properties at room temperature. The InP NW lasers can achieve repetitive switching between photoluminescence (PL) and lasing with an extinction ratio of 22‐fold by applying a gate voltage of 3 V using ionic liquid (IL) as a dielectric layer. IL brings forth ultra‐high capacitance due to the nanometer‐wide electric double layer (EDL) between interfaces, mapping out gating efficiency of ≈100‐fold compared to the conventional bottom gate configurations. This IL‐embedded nanolaser device can be a promising platform for the advanced integrated nanophotonic system.